Zinc tolerance and accumulation capability by Penicillium strains isolated from Neutral Mine Drainage (NDM) colloidal precipitates - Simone Di Piazza (Italian Journal of Mycology, 2018)
Zinc, at low concentration, is one of the oligo elements essential for life. As well as many others metals, high environmental Zn concentrations are toxic for several organisms and can compromise their lifecycle. Neutral (or alkaline) Mine Drainage (NMD) are metal-rich solutions with near-neutral pH values, often generated by weathering of sulphide minerals (mainly Zn and Pb sulphides), circulating in mining areas. As this phenomenon favours the dispersion of metals and contributes to the rising of concentration of toxic elements in the groundwaters, NMD threatens the surrounding environment. The effectiveness of autochthonous fungal strains in bioremediation process of ecotoxic metal is today well founded. We investigated the Zn tolerance and accumulation capability of four Penicillium strains (two P. janthinellum, one P. olsonii, and one P. waksmanii) isolated from an NMD environment. The experimental results showed a positive growth response of all strains at 750 ppm of Zn, while only two strains (P. olsonii and P. waksmanii) were able to grow at 1500 ppm of Zn. Further tests showed a bioaccumulation capability by P. olsonii strains up to 8600 ppm. These data, reporting the bioaccumulation capabilities of fungal species that have not been studied previously, are a further confirmation of the potential usefulness of autochthonous microfungi in bioremediation of heavy metals, and highlight the need of increase the number of tested strains.